IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MA AL AMIRIYYAH BLOKAGUNG BANYUWANGI - Fauzi, Moh. Nur; Sofwanti, Aisyah De (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2022)
The implementation of Academic Supervision is one of the important programs that must be carried out by the principal because there are still problems with academic supervision in educational institutions such as: suitability of implementation time, unpreparedness in supervision due to psychological aspects and there are still teachers who have not been able to make learning tools. This study aims to understand and analyze: (1) Implementation of Supervision by the Head of the Madrasah in Improving Teacher Performance at MA Al Amiriyyah (3) Improving teacher performance after academic supervision of the principal of the Madrasah at MA Al Amiriyyah. The research method used in this study is a descriptive method with a qualitative approach. The subjects of the research were the principal, the waka of curriculum, and the waka of public relations. Data collection methods are observation, interviews, and documentation. The data analysis technique is through the data reduction process, the data presentation process, and the conclusion drawing process. The results showed that: 1) The implementation of the academic supervision of the madrasah principal in improving teacher performance at MA Al Amiriyyah there were three processes, including planning for the madrasah principal's academic supervision based on increasing teacher competence and performance which was an analysis of the results of supervision in the previous year, the implementation carried out by the head of the madrasa with individual and group techniques, and evaluation of the teachers who have been supervised is carried out by the head of the madrasa or the supervisor of the educational institution in the learning process. 2) The performance of teachers at MA Al Amiriyyah has increased, after taking certification almost all of the teachers here have good performance, starting from preparing lesson plans, implementing the learning process, mastering learning materials, and using learning aid media tools.